2012
DOI: 10.1063/1.4724349
|View full text |Cite
|
Sign up to set email alerts
|

Charge accumulation at organic semiconductor interfaces due to a permanent dipole moment and its orientational order in bilayer devices

Abstract: Influence of the direction of spontaneous orientation polarization on the charge injection properties of organic light-emitting diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
164
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 36 publications
13
164
3
Order By: Relevance
“…Interface charge was first detected by Brütting et al at the a-NPD/Alq3 interface in a bilayer OLED. Furthermore, Ishii et al reported clear GSP behavior with a slope of 48 mV/nm, which corresponds to an interface charge density of 1.36 mC/m 2 [14]. In our study, the carrier accumulation at the TPD/C 60 interface was observed by the DMP analysis, which is similar to previous reports.…”
Section: Dmp Of P-n Heterostructured Opv Cellssupporting
confidence: 91%
“…Interface charge was first detected by Brütting et al at the a-NPD/Alq3 interface in a bilayer OLED. Furthermore, Ishii et al reported clear GSP behavior with a slope of 48 mV/nm, which corresponds to an interface charge density of 1.36 mC/m 2 [14]. In our study, the carrier accumulation at the TPD/C 60 interface was observed by the DMP analysis, which is similar to previous reports.…”
Section: Dmp Of P-n Heterostructured Opv Cellssupporting
confidence: 91%
“…Other polar electron transport materials exhibiting orientation polarization are TPBi (À1.1 mC/m . 36 There are two key advantages of the presented approach compared to other measurement techniques. First, the active layers to be investigated can be prepared and deposited in the same way and especially with the same thickness as in a regular OLED or solar cell stack; thus, the extracted mobility values can be assumed to be the same in the regular device.…”
Section: Discussionmentioning
confidence: 99%
“…35 Radiative recombination takes place in the emissive layer at the HTL/ETL interface, as soon as the applied voltage is large enough (>V bi ) to inject both charge carrier species into their respective transport layers. The most commonly used electron transport materials for OLEDs, like Alq 3 , TPBi, BCP, and BPhen, 36,37 exhibit a permanent macroscopic polarization due to spontaneous orientation of molecular dipoles upon layer deposition, forming an effective sheet charge density on both sides of the layer. 38 It has been shown that this polarization effect leads to a reduction of the hole injection voltage V t , dependent on the thickness of the ETL and on the interface charge density, according to the following equation: 33,34 …”
Section: Introductionmentioning
confidence: 99%
“…However, this value can be modified by different effects, such as Fermi-level pinning, spontaneous orientation polarization or band-bending phenomena. There are light-irradiation techniques to estimate V bi [53,54] or the method given by Mantri et al [55]. We follow this last method, in which an initial value of V bi is extracted from the transition voltage at which the slope of the J − V AC curve changes from exponential (diffusion regime) to power-law (space-charge-limited regime) (point D in Fig.…”
Section: Parameter Extraction and Verification -Darknessmentioning
confidence: 99%